Evaluation of Potential Drug Interaction of Analgesic in Cancer Patient Receiving Palliative Care in Dharmais Cancer Hospital - Sitepu, Eme Stepani; Puspitasari, Atika Wahyu; Azmi, Nuriza Ulul; Sari, Lila Nilam (UI Scholars Hub, 2020)
Analgesics are mostly used in cancer patients receiving palliative care to improve the quality of life of patients. Besides analgesics, cancer patients receiving palliative care were also given other drugs in combination to overcome other symptoms of cancer, and this combination could potentially cause drug interactions. This study was aimed to analyze the potential of drug interactions with analgesics in cancer patients. The study design was cross-sectional with a retrospective method and descriptive study. The sample of this study was cancer palliative care patient’s prescription at Dharmais Cancer Hospital in the period of January – December 2017. The sample analyzed in this study consisted of 273 prescriptions. This study found that there were 191 prescriptions (69.9%) of analgesics which potential- ly interacted with 316 interaction cases. Fentanyl and morphine with 61 cases (19.3%), morphine and gabapentin with 60 cases (18.9%) and morphine and amitriptyline with 33 cases (10.4%) were observed as the three most analgesics-other drugs interaction. Based on severity levels, there were 73.5% of major interaction, 26.3% of moderate interaction, and 0.2% of minor interaction. This study concluded that high occurrence of drug interactions was observed in analgesic drugs, therefore close monitoring is needed in cancer patient receiving palliative care.